Chiral phosphines in nucleophilic organocatalysis - Xiao, Yumei; Sun, Zhanhu; Guo, Hongchao; Kwon, Ohyun (Beilstein Journal of Organic Chemistry, 2014)
This review discusses the tertiary phosphines possessing various chiral skeletons that have been used in asymmetric nucleophilic organocatalytic reactions, including annulations of allenes, alkynes, and Morita–Baylis–Hillman (MBH) acetates, carbonates, and ketenes with activated alkenes and imines, allylic substitutions of MBH acetates and carbonates, Michael additions, γ-umpolung additions, and acylations of alcohols.
Keywords: asymmetric catalysis; chiral phosphine; nucleophilic; organocatalysis; organophosphorus; synthesis